Implementasi Perda No. 3 Tahun 2018 Tentang Penanggulangan Kemiskinan (Studi Kasus Di Desa Sukamandi Hilir Dusun Iv Kecamatan Pagar Merbau Kabupaten Deli Serdang) - Masita Devi; Indra Muda; Walid Mustafa (Universitas Medan Area, 2022)
Poverty alleviation is a policy of government and local government programs that are carried out systematically, planned, and in synergy with the business world and the community to reduce the number of poor people in order to improve the welfare of the people. This study aims to find out how the process of implementing policies on poverty reduction in Sukamandi Hilir Village is and to find out the inhibiting factors in implementing these policies. This type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation review. The data that has been collected is then tested for validity using data triangulation testing techniques. Data analysis includes data reduction, data presentation, and drawing conclusions. Based on the variables that influence the implementation of the policies proposed by Van Meter and van Horn, the implementation of Perda no. 3 of 2018 concerning poverty alleviation in Sukamandi Hilir Village, Dusun IV did not run optimally due to a lack of communication and coordination in the implementation process, this also caused several programs not to be implemented properly.